Longitudinal Relationship Between Frailty and Cognition in Patients 50 Years and Older with Breast Cancer. Issue 5 (29th April 2019) - Magnuson, Allison; Lei, Lianlian; Gilmore, Nikesha; Kleckner, Amber S.; Lin, Feng V.; Ferguson, Robert; Hurria, Arti; Wittink, Marsha N.; Esparaz, Benjamin T.; Giguere, Jeffrey K.; Misleh, Jamal; Bautista, Javier; et al.
Abstract : OBJECTIVES: To evaluate relationships between frailty and cognition longitudinally in adults 50 years and older with breast cancer receiving chemotherapy. DESIGN: Secondary analysis of a prospective longitudinal observational study. SETTING: University of Rochester NCI Community Oncology Research Program community oncology clinics. PARTICIPANTS: Patients with breast cancer age 50 and older receiving adjuvant/neoadjuvant chemotherapy (n = 376) and age‐matched controls without cancer (n = 234). MEASUREMENTS: Frailty was assessed using a modified frailty score from self‐reported assessments (weakness, exhaustion, physical activity, and gait speed). Cognition was assessed by patient report (Functional Assessment of Cancer Therapy‐Cognition [FACT‐Cog]) and objective measures. Frailty and cognition were measured at three time points (prechemotherapy [A1], postchemotherapy [A2], and 6 months postchemotherapy [A3]; similar time interval for controls). Linear regression models evaluated associations between frailty and cognition adjusting for covariates. RESULTS: The average age was 59 years (standard deviation = 6.4 y). At baseline, patients with cancer had a higher mean frailty score (1.21 vs .73; P < .001) and lower mean FACT‐Cog score (158.4 vs 167.3; P < .001) compared with controls. Objective cognitive measures were not statistically different. Longitudinal decline in FACT‐Cog between A1 and A2 ( P < .05) and between A1 and A3 ( P < .01) was associated with increased frailty score in patients compared with controls. Longitudinal worsening in Controlled Oral Word Association ( P < .05) and Trail‐Making Test ( P < .01) were associated with an increase in frailty between A1 and A2 in patients compared with controls; longitudinal decline in the Delayed Match to Sample test was associated with an increase in frailty between A1 and A3 ( P < .05) in patients compared with controls. This finding remained significant for a subset analysis of those aged 65 and older. CONCLUSION: In patients with breast cancer aged 50 and older, longitudinal decline in FACT‐Cog and objective measures of attention and memory were associated with increased frailty during treatment and up to 6 months posttreatment. Overall, our study suggests cognition and frailty are both important factors to assess in breast cancer patients. J Am Geriatr Soc 67:928–936, 2019.